RITUXIMAB TREATMENT EFFICACY IN PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS REFRACTORY TO STANDARD THERAPY IN THE LONG-TERM FOLLOW-UP - M. E. Tsanyan; S. K. Soloviev; A. V. Torgashina; E. N. Aleksandrova; S. G. Radenska-Lopovok; E. V. Nikolaeva; E. L. Nasonov (Научно-практическая ревматология, 2014)
Objective. To evaluate the efficacy and safety of rituximab (RTM) treatment in the long-term follow-up of patients with systemic lupus erythematosus (SLE) refractory to standard therapy. Material and methods. RTM therapy was prescribed to 97 SLE patients with high disease activity and insufficient effica- cy of using high doses of glucocorticoids (GC) and cytostatics. The median follow-up time (25th; 75th percentiles) was 18 [12; 36] months. The most common clinical manifestations of SLE included nephritis (62%), skin lesion (33%), and lesion of the nervous system (22.7%). The clinical assessment of the SLE activity was carried out using the SLEDAI-2K activity index. In assessing the therapy efficacy, the following concepts were used: the partial response (PR), complete response (CR), and flare. Flare was classified as moderate (MF) and severe (SF) using the SLE flare index (SFI). Results. Immediately after RTM therapy, depletion of B-cells was determined in 78% of the patients with SLE. During the 6-year follow-up, the effect of RTM therapy was achieved in 84% of the patients after repeated courses of RTM (CR – 56%, PR – 28%). In total, flares were observed in 24 (24.7%) patients; the median interval from RTM administration to flare was 12 [12; 24] months. In the long-term follow-up, the decline in the SLEDAI-2K index, normalization of laboratory test values, and the decrease in the daily GC dose were noted. Most patients tolerated well both the first and repeated courses of RTM therapy. Conclusion. According to the results of the long-term follow-up, RTM therapy is a highly effective method to treat SLE patients with the ineffectiveness of previously conducted standard therapy with GC and cytostatics. Good tolerance of RTM treatment has been noted; no increase in risk of infectious complications or adverse reactions has been found.